SOX2 promotes tumor growth of esophageal squamous cell carcinoma through the AKT/mammalian target of rapamycin complex 1 signaling pathway. Issue 7 (16th April 2013) - Gen, Yasuyuki; Yasui, Kohichiroh; Nishikawa, Taichiro; Yoshikawa, Toshikazu
Abstract : The transcription factor SOX2 is essential for the maintenance of embryonic stem cells and normal development of the esophagus. Our previous study revealed that the SOX2 gene is an amplification target of 3q26.3 in esophageal squamous cell carcinoma (ESCC), and that SOX2 promotes ESCC cell proliferation in vitro . In the present study, we aimed to identify the mechanisms by which SOX2 promotes proliferation of ESCC cells. Using a phosphoprotein array, we assayed multiple signaling pathways activated by SOX2 and determined that SOX2 activated the AKT/mammalian target of rapamycin complex 1 (mTORC1) signaling pathway. LY294002, an inhibitor of phosphatidylinositol 3‐kinase, and rapamycin, an inhibitor of mTORC1, suppressed the ability of SOX2 to enhance proliferation of ESCC cells in vitro . Effects of SOX2 knockdown, including reduced levels of phosphorylated AKT and decreased ESCC cell proliferation, were reversed with constitutive activation of AKT with knockdown of phosphatase and tensin homolog. In mouse xenografts, SOX2 promoted in vivo tumor growth of ESCC, which was dependent on AKT/mTORC1 activation. LY294002 suppressed the ability of SOX2 to enhance tumor growth of ESCC by reducing cell proliferation, but not by enhancing apoptosis. Furthermore, tissue microarray analysis of 61 primary ESCC tumors showed a positive correlation between expression levels of SOX2 and phosphorylated AKT. Our findings suggest that SOX2 promotes in vivo tumor growth of ESCC through activation of the AKT/mTORC1 signaling pathway, which enhances cell proliferation.